2019
DOI: 10.1016/j.tjem.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Lactate measurements accurately predicts 1-week mortality in emergency department patients with acute kidney injury

Abstract: BackgroundStudies on prognostic indicators in patients with acute kidney injury are limited. This study investigated 1-week mortality, laboratory and clinical parameters according to the lactate levels in patients with acute kidney injury.MethodsIn this cross-sectional study, we compared the lactate levels on admission and follow-up in emergency department with vital findings, laboratory parameters, and 1-week mortality.ResultsData of 3375 patients examined; 2681 patients excluded and 694 patients were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The analysis of longitudinal submodel indicated that the use of CRRT tends to increase lactate levels within 28 days, while the joint modeling of longitudinal and survival data indicated that lactate level changes were associated with mortality and that log(lactate) is a risk factor for 28-day mortality in S-AKI patients. Many studies have confirmed lactate as a powerful biomarker for sepsis with renal damage and can accurately predict mortality [ 23 25 ]. Reducing lactate is therefore a vital procedure for improving the likelihood of patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of longitudinal submodel indicated that the use of CRRT tends to increase lactate levels within 28 days, while the joint modeling of longitudinal and survival data indicated that lactate level changes were associated with mortality and that log(lactate) is a risk factor for 28-day mortality in S-AKI patients. Many studies have confirmed lactate as a powerful biomarker for sepsis with renal damage and can accurately predict mortality [ 23 25 ]. Reducing lactate is therefore a vital procedure for improving the likelihood of patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of longitudinal submodel indicated that the use of CRRT is associated with increases in lactate levels within 28 days, while the joint modeling of longitudinal and survival data indicated that lactate level changes were associated with mortality and that log(lactate) is a risk factor for 28-day mortality in S-AKI patients. Many studies have con rmed lactate as a powerful biomarker for sepsis with renal damage and can accurately predict mortality [23][24][25] . Reducing lactate is therefore a vital procedure for improving the likelihood of patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…2 Studies have consistently demonstrated that high lactate level and low lactate clearance are associated with poor prognosis in many clinical cases, such as sepsis, trauma, shock, and cardiac arrest. [3][4][5][6] Particularly in sepsis and septic shock, a lactate value over 4.0mmol/L has been widely researched and linked to increased mortality. 7,8 In subsequent studies on sepsis, a lactate value above 2.0mmol/L has also been identified as a warning sign for poor prognosis.…”
Section: Introductionmentioning
confidence: 99%